Some Existence Results for a System of Nonlinear Fractional Differential Equations - Ameer, Eskandar; Aydi, Hassen; Isik, Huseyin; Nazam, Muhammad; Parvaneh, Vahid; Arshad, Muhammad (Hindawi Ltd, 2020)
In this paper, we show that a sequence satisfying a Suzuki-type JS-rational contraction or a generalized Suzuki-type Ciric JS-contraction, under some conditions, is a Cauchy sequence. This paper presents some common fixed point theorems and an application to resolve a system of nonlinear fractional differential equations. Some examples and consequences are also given.
Aydi, Hassen/0000-0003-4606-7211; Parvaneh, Vahid/0000-0002-3820-3351; Isik, Huseyin/0000-0001-7558-4088; Arshad, Muhammad/0000-0003-3041-328X